Virally inactivated human platelet concentrate lysate induces regulatory T cells and immunosuppressive effect in a murine asthma model. Issue 9 (11th January 2013) - Lee, Yueh‐Lun; Lee, Lin‐Wen; Su, Chen‐Yao; Hsiao, George; Yang, Yi‐Yuan; Leu, Sy‐Jye; Shieh, Ying‐Hua; Burnouf, Thierry
<x xml:space="preserve">Abstract</x> Background Platelet concentrate lysates (PCLs) are increasingly used in regenerative medicine. We have developed a solvent/detergent (S/D)‐treated PCL. The functional properties of this preparation should be unveiled. We hypothesized that, due to transforming growth factor‐β1 (TGF‐β1) content, PCLs may exert immunosuppressive and anti‐inflammatory functions. Study Design and Methods PCL was prepared by S/D treatment, oil extraction, and hydrophobic interaction chromatography. The content of TGF‐β in PCL was determined by enzyme‐linked immunosorbent assay. Cultured CD4+ T cells were used to investigate the effects of PCL on expression of transcription factor forkhead box P3 (Foxp3), the inhibition of T‐cell proliferation, and cytokine production. The regulatory function of PCL‐converted CD4+ T cells was analyzed by suppressive assay. The BALB/c mice were given PCL‐converted CD4+ T cells before ovalbumin (OVA) sensitization and challenge using an asthma model. Inflammatory parameters, such as the level of immunoglobulin E (IgE), airway hyperresponsiveness (AHR), bronchial lavage fluid eosinophils, and cytokines were assayed. Recombinant human (rHu) TGF‐β1 was used as control. Results PCL significantly enhanced the development of CD4+Foxp3+‐induced regulatory T cells (iTregs). Converted iTregs produced neither Th1 nor Th2 cytokines and inhibited normal T‐cell proliferation. PCL‐ and rHuTGF‐β‐converted CD4+ T cells prevented OVA‐induced asthma. PCL‐ and rHuTGF‐β‐modified T cells both significantly reduced expression levels of OVA‐specific IgE and significantly inhibited the development of AHR, airway eosinophilia, and Th2 responses in mice. Conclusion S/D‐treated PCL promotes Foxp3+ iTregs and exerts immunosuppressive and anti‐inflammatory properties. This finding may help to understand the clinical properties of platelet lysates.